On the contribution of parental expectations to the academic progress of youngsters - Marcenaro-Gutiérrez, Óscar David; Prieto-Latorre, Claudia; López-Agudo, Luis Alejandro (Elsevier, 2025)
This paper analyses whether parental expectations play a relevant role in determining students’ progression from primary to secondary education in maths and reading. Taking advantage of longitudinal census data for the Spanish region of Andalusia, we propose alternative identification strategies to estimate the influence of expectations on students’ academic success. We tackle the endogeneity problem of expectations by employing time fixed-effects and applying an instrumental variables procedure, which uses a proxy of students’ ability. The results confirm that higher parental expectations positively associate with students’ achievement. Expectations are found to be a more important predictor of children’s performance in reading than in mathematics, while performance in mathematics depends to a larger extent on innate students’ ability. Additionally, we have found that boys’ academic performance is more sensitive to parental expectations, while parents have higher educational expectations for girls. This higher parental exigency for girls in comparison to boys may be a sign of the permanence of gender roles in society.
Keywords: Rendimiento académico - Modelos matemáticos; Familia y enseñanza; Expectations; Academic achievement; Census; Gender; Parents